Local Knowledge of Traditional Medicine and Ethnic Food Duano, Kerinci and Suku Anak Dalam Jambi As a Natural Science Learning Resource - Mustakim, Ardi; Hariyadi, Bambang; Hamidah, Afreni; Falani, Ilham (Integrated Science Education Journal, 2024)
Purpose of the study: The aim of this research is to explore the concept of science (biology, physics, and chemistry) in traditional ethnic medicine and food of the Duano, Kerinci, and Suku Anak Dalam Jambi. Methodology: This research examines the concept of science based on traditions and local knowledge as a source of science learning (biology, chemistry, and physics). Type of qualitative research with an ethnographic approach. Data was collected through observation, interviews, FGD, and documentation using Spradley model data analysis. Main Findings: The research found that the Duano Dalam tribe has local traditions and knowledge, such as menorah sunburn, marine ecology, lung, and gulai making. The Kerinci tribe has local knowledge about ethnic medicine and food, including Betemas/Tasapa and surian chili sauce. Meanwhile, the Anak Dalam (SAD) tribe has a tradition of Besale and local knowledge of Batangas and fish Pekasam food. The collection of traditions and local knowledge of each tribe has the potential to become a basis for science concepts in learning. Novelty/Originality of this study: The novelty or originality of the research entitled “Local Knowledge of Traditional Medicine and Ethnic Food of the Duano, Kerinci, and Anak Dalam Tribes as a Natural Science Learning Resource" lies in several key aspects. These aspects are 1) Local traditions and knowledge that can be used as a basis for science learning, 2) cultural and ethnographic perspectives as sources of science learning, 3) Interdisciplinary approaches, 4) Cross-Cultural Learning Potential, and 5) Conservation and Sustainable Practices.